OP0194-HPR Nursing Triage in Rheumatology: Three Months Experience in An Outpatient Clinic of The University of Florence (Italy). (15th July 2016) - Piemonte, G.; El Aoufi, K.; Braschi, F.; Poli, M.; Guiducci, S.; Bellando Randone, S.; Rasero, L.; Matucci Cerinic, M.
Abstract : Background: At present patients with rheumatic diseases are mainly assisted in outpatient settings. In our centre more than 150 patients with SSc (Systemic Sclerosis) and more than 100 patients with SPA (Spondyloathritis) are treated monthly. Rheumatic diseases are chronic conditions associated with disability, reduced quality of life and emotional and social consequences. Nurses' role is crucial in improving rheumatic patients' global health providing educational support, promoting self-management and helping accessing appropriate services when needed. Objectives: To describe nursing triage in rheumatology – A nurse led service focused in monitoring disease activity, symptoms and complications and providing educational and clinical support. Nursing triage takes place before rheumatologists' assessment. Period of observation: 1/12/2013 – 28/2/2014 Methods: All SSc and VEDOSS patients were evaluated for Raynaud Condition Score (RCS), sHAQ, SScQoL, HAMIS, Cochin, Borg, IIEF5. DUs and other skin lesions were assessed. All SPA patients were evaluated for MASES, BASMI, BASDAI, BASFI, swollen and tender joints, tender points and sacroiliac joint pain. BP, BMI were available for all patients. A severity index based on the previous tests' scorings was obtained both for SSc and SPA patients. Severity index for SSc/VEDOSS was based on DUs presence, sHAQ, HAMIS, Cochin, Borg, RCS and ranges between 0 and 7 (0=lowest severity; 7=highest severity). Severity index for SPA was based on all the previous evaluations and ranges between 0 and 10 (0= lowest severity; 10= highest severity). Results: 264 patients were treated in SSc/VEDOSS outpatient clinic (51 VEDOSS, 71 SSc, 7 primary RP, 98 secondary RP whose diagnosis had to be confirmed). DUs occurred in 29, 41% of SSc patients, in 4, 08% of patients with secondary RP, no DUs were found in VEDOSS patients. DUs were significatively associated with global and hand impairment and with reduced QoL (p<0, 05). In SSc patients severity index, RP severity, overall and hand disability were more severe than VEDOSS patients (p<0, 05). SPA patients had a mean severity index of 3, 85; ds 2, 67. The overall disability was low (BASFI mean value 2, 32; ds 2, 56), the disease activity was high (BASDAI mean value=4, 09; ds 2, 62). Conclusions: SSc and VEDOSS patients with severity index=0 and SPA patients with severity index≤1 may be followed mainly by nursing staff with interventions based on lifestyle modifications and non-pharmaceutical therapies. Adequate protocols must be approved by rheumatologists staff. In this context a nurse led helpline may be effective to select the most appropriate site and level of care for acute conditions in rheumatic diseases. References: Amanzi L et al. Digital ulcers in scleroderma: staging, characteristics and subsetting through observation of 1614 digital lesions. Rheumatology. 2010 Jul; 49(7): p. 1374–82 Pope J. Measures of Systemic Sclerosis, Scleroderma Arthritis Care Res (Hoboken). 2011 Nov; 63 Suppl 11: S98–111 Disclosure of Interest: None declared